The International and Political Journal: The Russian-Ukrainian Conflict and The Energy Crisis in the International Markets - Auda, Lecturer .Dr.Zaman Majed (The International and Political Journal, 2024)
The Russian-Ukrainian conflict has had repercussions on the global economy in general and on the energy sector in particular. The conflict was seen as a real threat to energy security and international markets, especially after the imposition of economic sanctions and the embargo on Russian energy supplies. Which led to a sharp rise in energy prices, disruptions in supply and demand, disruption of supply chains, and then to a decline in the global growth rate, a decrease in global gross product and per capita national income, a decline in the value of hard currencies for some countries, an increase in economic inflation rates, and the cessation of many energy-dependent economic sectors in most countries of the world.